More Bywords - Yonge, Charlotte M. (Charlotte Mary), 1823-1901 (Salt Lake City, UT : Project Gutenberg, 2004)
"More Bywords" by Charlotte M. Yonge is a collection of historical tales and narratives likely written during the late 19th century. The stories draw upon themes of conflict, cultural interactions, and moral lessons set against the backdrop of significant historical events, such as the early Christian Church and the struggles faced by protagonists in various eras. The opening of this collection introduces the first tale, "The Price of Blood," where we find ourselves in the midst of a procession seeking divine protection for their fields amidst fear of war and famine. Set in the region of Auvergne, the narrative depicts the interplay between Romans and Goths, showcasing characters like Marcus AEmilius Victorinus, a senator, and his friend, Sidonius Apollinaris, who grapple with the implications of impending violence on their community. As tensions rise following the actions of the young Arvernian leader, Verronax, the story unfolds around themes of justice, blood feuds, and the impact of personal oaths amidst a tumultuous social backdrop, setting the stage for deeper explorations of moral duty and sacrifice within the ensuing tales. (This is an automatically generated summary.)
The price of blood -- The cat of cat copse -- De facto and de jure -- Sigbert's guerdon -- The beggar's legacy -- A review of nieces -- Come to her kingdom -- Mrs. Batseyes -- Chops.
Release date is 2004-04-01
Transcribed by David Price
Keywords: Poetry; Short stories